EFEKTIVITAS ORGANISASI PEMERINTAH DESA DALAM MENERAPKAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA PONDOK SUGUH KABUPATEN MUKOMUKO - Dovista, Serly; Hakim, Kahar; Nursanty, Nursanty (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
The Village Financial System will make it easier for the Village Government to prepare village programs and will support the realization of transparent, accountable and trustworthy government. However, in its implementation, the SISKEUDES application still has problems that must be resolved by village government officials. This research aims to determine the achievement of objectives as an illustration of the effectiveness of the Pondok Suguh Village Government in implementing the SISKEUDES application. The method used in this research is descriptive qualitative to provide an overview of the research problem. The aspects of this research use the theory of organizational effectiveness according to Etzioni quoted by Indrawijaya (2014: 187) with aspects of adaptation, integration, motivation, production. The research results show that in the Adaptation aspect, the Pondok Suguh Village Government has been able to adapt to every version change that occurs, but before and since the implementation of the SISKEUDES application there have been no significant changes to work space facilities. In the Integration Aspect, there has been a mutual agreement between the community and the Village government. Pondok Suguh, but the socialization and technical guidance as well as coordination with other organizations cannot be said to be going well. The Motivation aspect has shown a willingness to try as best as possible and the infrastructure is also complete. Then, in the aspect of production, quantity and quality of output, the Pondok Suguh Village Government has succeeded in achieving the predetermined time target. Then also in the data input stage, the Pondok Suguh Village Government felt that it was very easy and made financial management structured and directed. Therefore, it can be concluded that although there are several things that must be improved in order to maintain the effectiveness of the village government in implementing the SISKEUDES application, the Pondok Suguh Village Government has succeeded in achieving its stated goal, namely completing financial reports that are easier, more focused and more appropriate. with a predetermined target time, so that in the end the implementation of the SISKEUDES application in Pondok Suguh Village can be said to be effective.